A subdomain in the transmembrane domain is necessary for p185neu* activation. - Cao, H (1992)
The neu proto-oncogene encodes a protein highly homologous to the epidermal growth factor receptor. The neu protein (p185) has a molecular weight of 185,000 Daltons and, like the EGF receptor, possesses tyrosine kinase activity. neu is activated in chemically induced rat neuro/glioblastomas by substitution of valine 664 with glutamic acid within the transmembrane domain. The activated neu* protein (p185*) has an elevated tyrosine kinase activity and a higher propensity to dimerize, but the mechanism of this activation is still unknown. We have used site-directed mutagenesis to explore the role of specific amino acids within the transmembrane domain in this activation. We found that the lateral position and rotational orientation of the glutamic acid in the transmembrane domain does not correlate with transformation. However, the primary structure in the vicinity of Glu664 plays a significant role in this activation. Our results suggest that the Glu664 activation involves highly specific interactions in the transmembrane domain of p185.